Perancangan Safety Lock pada Brangkas Uang Berbasis Arduino Uno dengan QR Scanner GM 65 dan Sensor Fingerprint AS608 - Alvin Zuhair; Antika Prasetyaningtyas; Muhammad Syukron; Kukuh Trisna Pambudia; Faisal Hafizh Purnomo (Universitas Merdeka Malang, 2025)
As crime rates rise and technology advances, security systems are becoming an essential necessity to protect assets and valuables. Conventional locks, which are easy to break into, lose, and duplicate, are no longer effective in maintaining security. As a solution, digital access systems such as the GM65 QR Code Sensor and AS608 fingerprint sensor are used to secure safes. Both technologies offer more practical, secure, and efficient access compared to conventional locks. The Sensor high performance in reading QR Codes, while the fingerprint sensor provides a permanent level of security, although it has limitations in wet or dusty conditions. The experimental results show that the success of opening the safe is influenced by the clean condition of the fingerprint and the proper distance of the barcode sensor. This research aims to improve the effectiveness of security systems by incorporating digital technology to prevent unauthorized access and protect valuable data.